Comparison on micromechanical properties of interfacial transition zone in concrete with iron ore tailings or crushed gravel as aggregate. (15th October 2021) - Feng, Weipeng; Dong, Zhijun; Jin, Yu; Cui, Hongzhi
Abstract: Using recycling iron ore tailings (IOTs) from industrial solid waste as concrete aggregates agrees with the sustainable development of the construction industry and carbon neutrality commitment. As the interfacial transition zone (ITZ) between IOTs and cement paste is significant to concrete performance but rarely studied, the present work is focused on the micromechanical property of ITZ in concrete with IOTs. Comparative studies were conducted on ITZ of IOTs concrete and crushed gravel (natural aggregate, NA) concrete by statistical grid nanoindentation technique, scanning electron microscope (SEM), atomic force microscope (AFM), energy dispersive spectroscopy (EDS), and micro indentation. Maximum likelihood estimation (MLE) method with the expectation-maximization (EM) algorithm was adopted as a deconvolution technique to find the optimized parameters of the two-dimensional Gaussian mixture model (GMM) for the nanoindentation data. With the errors from −8.6% to +1.7% of the two-dimensional GMM for phases identification, results show that ITZ of IOT samples have much higher volume fractions of LD-C-S-H phase, HD-C-S-H phase, CH phase and even the UHD-C-S-H phase compared to NA samples. The hydrated phase assemblage of IOT samples was further proved by micro indentation to formed a denser microstructure in ITZ with enhanced bonding properties of reduced modulus  M  = 8.13 GPa and hardness H  = 0.44, compared to M  = 6.63 GPa and H  = 0.37 of NA samples. According to the results, because of the local low water-binder ratio, ITZ of IOTs concrete showed a denser microstructure and higher micromechanical properties than NA concrete. This study presented a theoretical ground for recycling IOTs as aggregate in concrete.